Case report: Desquamating dermatitis, bilateral cerebellar lesions in a late-onset methylmalonic acidemia patient - Chen, Qihua; Tang, Jianguang; Zhang, Hainan; Qin, Lixia (Frontiers in Neurology, 2023)
Introduction: Cobalamin C (cblC) deficiency is a rare hereditary disorder affecting intracellular cobalamin metabolism, primarily caused by mutations in MMACHC. This condition is characterized by combined methylmalonic acidemia and hyperhomocysteinemia, displaying a wide range of clinical manifestations involving multiple organs. Owing to its uncommon occurrence and diverse clinical phenotypes, diagnosing cblC deficiency is challenging and often leads to delayed or missed diagnoses. Case description: In this report, we present a case of late-onset cblC deficiency with brown desquamating dermatitis on the buttocks. Magnetic resonance imaging (MRI) of the brain revealed bilateral cerebellar abnormalities. The suspicion of an inherited metabolic disorder was raised by abnormal serum amino acid and acylcarnitine levels, along with increased urine methylmalonic acid and serum homocysteine levels. Whole-exome sequencing helped identify a homozygous variant (c.482G>A) in MMACHC, confirming the diagnosis of cblC deficiency. However, despite receiving treatment with hydroxocobalamin and betaine, the patient did not experience clinical improvement, which may be attributed to the delayed diagnosis as indicated by the declining homocysteine and methylmalonic acid levels. Conclusion: Collectively, we emphasize the significance of recognizing the skin lesions and observing serial MRI changes in patients with cblC deficiency. Our case underscores the importance of early diagnosis and timely therapeutic intervention for this severe yet frequently manageable condition.